COLLECTIVE HUMAN RIGHTS AND THE PROBLEM OF THEIR NORMATIVE ENFORCEMENT - Гатамов, Хатаі Севіндік огли (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: substantiation of the necessity of normative and legal consolidation of collective human rights. Methods of research: analysis and study of international legal documents that contain provisions on collective human rights. Results: the normative and practical utility of consolidating collective human rights into international legal acts. Collective rights are not individual, as they belong to groups, collectives, peoples as a whole. These rights have certain characteristics that distinguish them from the rights of individuals and which allow us to see their qualitatively different legal nature, and not just «collective aspects». The use of collective rights is based on the subordination of the subordination of the minority to the majority, the exercise of individual rights occurs at the discretion of the individual. As practice shows, individual rights can not provide adequate protection for individual social collectives. Individual human rights do not provide adequate protection of the rights of indigenous peoples in respect of the territories that these peoples traditionally occupy. The customary ownership (individual right) of land has little in common with that age-old bond that connects, for example, the Indian tribe with a certain territory. The identity of indigenous peoples, their culture include the land on which they live. Therefore, it would be a dangerous delusion to try to regulate the relations associated with this land, the standard rules on the right of ownership. Collective rights belong to a group of individuals, united by some objective characteristics. Collective rights belong to the group as a whole, therefore its individual members can neither exercise nor protect these rights, unless they are authorized by the group itself. Discussion: proposal inclusion of this issue in the agenda of international organizations.